2010
DOI: 10.1016/j.jfms.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Mastocytaemia in cats: Prevalence, detection and quantification methods, haematological associations and potential implications in 30 cats with mast cell tumours

Abstract: The significance of mastocytaemia in cats is different from that in dogs because it appears exclusively associated with mast cell neoplasia. The prevalence of mastocytaemia was 0.05% of all feline submissions to a private laboratory and 43% in cats with mast cell neoplasia. None of 30 healthy cats had mastocytaemia. There was no sex bias or significant age difference between mastocytaemic and non-mastocytaemic cats with mast cell tumours (MCT). Buffy coat (BC) examination was the best screening method for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 18 publications
1
28
2
Order By: Relevance
“…3 Therefore, in cats, detection of mast cells in the blood is a useful diagnostic tool for mast cell neoplasia. 1,9 In the current case, peripheral blood smear analysis revealed a circulating atypical mastocytic population, strongly suggestive of mast cell neoplasia and explaining the moderate leukocytosis observed on the CBC. This finding emphasizes the importance of peripheral blood smear evaluation in hematologic evaluation in exotic species.…”
Section: Brief Communicationmentioning
confidence: 49%
See 1 more Smart Citation
“…3 Therefore, in cats, detection of mast cells in the blood is a useful diagnostic tool for mast cell neoplasia. 1,9 In the current case, peripheral blood smear analysis revealed a circulating atypical mastocytic population, strongly suggestive of mast cell neoplasia and explaining the moderate leukocytosis observed on the CBC. This finding emphasizes the importance of peripheral blood smear evaluation in hematologic evaluation in exotic species.…”
Section: Brief Communicationmentioning
confidence: 49%
“…3,9,12 In one study, circulating mast cells were not identified in clinically normal cats or ill cats without mast cell tumor-related disease. 3 Therefore, in cats, detection of mast cells in the blood is a useful diagnostic tool for mast cell neoplasia.…”
Section: Brief Communicationmentioning
confidence: 99%
“…An earlier study found no mast cells during evaluation of BC smears from 40 healthy and 40 ill cats without mast cell tumor (MCT), concluding that mastocytemia is a very rare finding in healthy cats and in cats with non‐MCT‐related diseases . In contrast, bone marrow or BC involvement is reported in up to 100% of cats with systemic MCT . These findings support the value of the practice of BC evaluation for MCT staging in cats.…”
Section: Introductionmentioning
confidence: 73%
“…Detection of circulating mast cells during blood smear (BS) or buffy coat (BC) evaluation is a rare finding in cats, with an overall reported incidence of 0.05% . An earlier study found no mast cells during evaluation of BC smears from 40 healthy and 40 ill cats without mast cell tumor (MCT), concluding that mastocytemia is a very rare finding in healthy cats and in cats with non‐MCT‐related diseases .…”
Section: Introductionmentioning
confidence: 99%
“…The staging approach to feline MCT has not been standardly defined as in dogs; staging for canine patients includes assessing regional lymph nodes with cytology, abdominal ultrasound ±liver and spleen cytology, and thoracic radiographs. While not useful in the dog, buffy coat screening may be more helpful in the cat as mastocytosis is caused almost entirely by mast cell neoplasia (Skeldon and others 2010). Its role in peripheral feline mast cell disease is undefined.…”
Section: Introductionmentioning
confidence: 99%